Part 4. Clinical Practice Guideline for Surveillance and Imaging Studies of Trauma Patients in the Trauma Bay from the Korean Society of Traumatology - Sung Wook Chang; Kang Kook Choi; O Hyun Kim; Maru Kim; Gil Jae Lee; Korean Society of Traumatology (KST) Clinical Research Group (Journal of Trauma and Injury)
The following recommendations are presented herein: All trauma patients admitted to the resuscitation room should be constantly (or periodically) monitored for parameters such as blood pressure, heart rate, respiratory rate, oxygen saturation, body temperature, electrocardiography, Glasgow Coma Scale, and pupil reflex (1C). Chest AP and pelvic AP should be performed as the standard initial trauma series for severe trauma patients (1B). In patients with severe hemodynamically unstable trauma, it is recommended to perform extended focused assessment with sonography for trauma (eFAST) as an initial examination (1B). In hemodynamically stable trauma patients, eFAST can be considered as the initial examination (2B). For the diagnosis of suspected head trauma patients, brain computed tomography (CT) should be performed as an initial examination (1B). Cervical spine CT should be performed as an initial imaging test for patients with suspected cervical spine injury (1C). It is not necessary to perform chest CT as an initial examination in all patients with suspected chest injury, but in cases of suspected vascular injury in patients with thoracic or high-energy damage due to the mechanism of injury, chest CT can be considered for patients in a hemodynamically stable condition (2B). CT of the abdomen is recommended for patients suspected of abdominal trauma with stable vital signs (1B). CT of the abdomen should be considered for suspected pelvic trauma patients with stable vital signs (2B). Whole-body CT can be considered in patients with suspicion of severe trauma with stable vital signs (2B). Magnetic resonance imaging can be considered in hemodynamically stable trauma patients with suspected spinal cord injuries (2B).